2020
DOI: 10.1007/s00417-020-04901-7
|View full text |Cite
|
Sign up to set email alerts
|

Descemet membrane endothelial keratoplasty (DMEK): clinical results of precut versus surgeon-cut grafts

Abstract: Purpose This study aims to investigate possible differences in clinical outcomes between precut and surgeon-cut grafts for Descemet membrane endothelial keratoplasty (DMEK). Methods 142 consecutive patients who underwent DMEK were included in the study. 44 patients received precut tissues, and 98 patients received surgeon-cut tissues. Precut grafts were allocated to the patient by the German Society for Tissue Transplantation if available. We compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
1
0
0
Order By: Relevance
“…Regarding these factors, our analyses are inconclusive. Regarding preparation techniques, our results are consistent with previous studies that found no difference between pre-cut and surgeon-cut tissues 13 , 15 . Graft marking was associated with an increased risk of detachment in the Lasso model only.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding these factors, our analyses are inconclusive. Regarding preparation techniques, our results are consistent with previous studies that found no difference between pre-cut and surgeon-cut tissues 13 , 15 . Graft marking was associated with an increased risk of detachment in the Lasso model only.…”
Section: Discussionsupporting
confidence: 92%
“…DMEK is considered the most up to date EK procedure choice in Western countries [ 3 ], although the collection of inserted Descemet’s endothelium lamella (14–20 μm) requires a long learning curve [ 53 , 54 ]. Immune rejection is drastically cut down to 1% (C.I.…”
Section: Resultsmentioning
confidence: 99%
“…No significant changes have been reported, but a reduction trend in rejection risk has been unveiled by our analysis (Figure 3). DMEK is considered the most up to date EK procedure choice in Western countries [3], although the collection of inserted Descemet's endothelium lamella (14-20 µm) requires a long learning curve [53,54]. Immune rejection is drastically cut down to 1% (C.I.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation